Predicting Treatment Success : Assessing Theoretically-Driven Constructs that Impact the Management of Type 2 Diabetes Mellitus Among African American Women in a Novel Peer-Delivered Small Changes Treatment Approach - DiNatale, Emily (East Carolina University, 2014)
Rural African American women have greater prevalence of Type 2 Diabetes Mellitus (T2DM) and poorer treatment outcomes compared to Caucasians. Some research suggests that self-efficacy, subjective norms, and locus of control (LOC) impact this population differently and may be linked to behavioral treatment outcomes. However, these relationships have not been directly examined. EMPOWER, a culturally-tailored T2DM intervention that utilizes community health workers (CHWs) to provide patient-centered care using a Small Changes Model (SCM), was developed as an innovative treatment approach for African American women. This study was designed to explore the best predictors of treatment success within the EMPOWER program and to determine whether self-efficacy, subjective norms, and LOC impact outcomes.   Assessments utilized program results of two hundred middle aged (age=53.45±10.24) obese (BMI=37.67±8.02) African American women with poorly-controlled diabetes (HbA1c=9.09±1.83) enrolled in EMPOWER. Half (n=102) were randomly assigned to a phone-based EMPOWER group while half (n=98) were assigned to a mail-based didactic comparative group. Weight, HbA1c, medication adherence, self-care behaviors, self-efficacy, and depression were measured at 0, 6, and 12-months. At 12-month follow-up, subjective norms and LOC were measured. Repeated measures ANOVAs indicated that both groups had a reduction in weight F(1.82, 197)=4.15, p=0.020, but no changes in HbA1c. Independent samples t-tests revealed a significant difference in God LOC between the EMPOWER group (M=19.16, SD=8.20) and the Mail group (M=22.42, SD=7.48; t(143)=-2.49, p=0.014) and between participants who used insulin (M=21.86, SD=7.55) and those who do not (M=18.88, SD=8.21; t(139)=-2.18, p=0.031). Theoretically-based moderated-mediation models assessed self-efficacy and subjective norms as mediators and God and Internal LOC as moderators of outcomes. While no mediation interactions were found, models revealed that subjective norms significantly impacted self-care behavior change (ß=1.48, p=0.037). God LOC served as a moderator that enhanced this relationship (ß=0.078, p=0.013). Results suggest that subjective norms may play a more important role in diabetes management behavior change among African American women than previously understood. Further, God LOC was shown to be an important and complex treatment factor that likely relates to both internal and external LOC. These findings have important implications for future health behavior change programs for African American women.
Keywords: Psychology; Spirituality; Health care management; Patient compliance; Diabetics--Attitudes; Diabetes in women; Rural African Americans--Diseases